THE EFFECT OF DIVERSE IODINE FERTILIZATION ON NITRATE ACCUMULATION AND CONTENT OF SELECTED COMPOUNDS IN RADISH PLANTS (Raphanus sativus L.) - Piotr Strzetelski; Sylwester Smoleń; Stanisław Rożek; Włodzimierz Sady (Acta Scientiarum Polonorum: Hortorum Cultus, 2010)
Plant fertilization with iodine may be an alternative source of this element in human diet. Iodine influence on nitrogen metabolism in plants has not yet been thoroughly described. Thus, there is an urgent need to determine the effect of iodine application on nitrate(V) accumulation in plants. The aim of the study was to determine the influence of soil and foliar application of iodine forms (I-, IO3-) on nitrate accumulation and concentration of selected compounds in radish plants. The following treatments were applied in the experiment: 1 – control (without application of iodine), 2 – foliar application in KI form, 3 – foliar application in KIO3 form, 4 – soil fertilization in KI form, 5 – soil fertilization in KIO3 form, 6 – soil fertilization in KI form + foliar application in KI form, 7 – soil fertilization in KIO3 form + foliar application in KIO3 form. Soil fertilization with iodine was carried out before radish sowing to the level of 15 mg I·dm-3 soil. Foliar application of this element was performed twice using iodine solution in a concentration per pure element of 0.2%, in dose of 0.4 dm3· m-2. In all tested combinations with iodine treatment an increase of ammonium ion content in radish roots was observed in comparison to the control. Both, foliar nutrition with KI as well as nitrogen fertilization with KIO3 (combination 2 and 6, respectively) resulted in a significant increase of free amino acids concentration in radish roots. No significant influence of tested factors was noted for the root and leaf content of: dry mass, nitrates(V), nitrates(III) as well as root level of total soluble sugars and leaf concentration of photosynthetic pigments and ammonium ions in radish.